Brentuximab vedotin with chemotherapy for stage III or IV classical Hodgkin lymphoma (ECHELON-1): 5-year update of an international, open-label, randomised, phase 3 trial - Straus, David J; Długosz-Danecka, Monika; Connors, Joseph M; Alekseev, Sergey; Illés, Árpád; Picardi, Marco; Lech-Maranda, Ewa; Feldman, Tatyana; Smolewski, Piotr; Savage, Kerry J; Bartlett, Nancy L; Walewski, Jan; et al. (The Lancet. Haematology, 2021)
Despite advances in the treatment of Hodgkin lymphoma with the introduction of PET-adapted regimens, practical challenges prevent more widespread use of these approaches. The ECHELON-1 study assessed the safety and efficacy of front-line A+AVD (brentuximab vedotin, doxorubicin, vinblastine, and dacarbazine) versus ABVD (doxorubicin, bleomycin, vinblastine, and dacarbazine) in patients with stage III or IV classical Hodgkin lymphoma. The primary analysis showed improved modified progression-free survival with A+AVD. We present an updated analysis of ECHELON-1 at 5 years, an important landmark for this patient population. ECHELON-1 was an international, open-label, randomised, phase 3 trial done at 218 clinical sites, including hospitals, cancer centres, and community clinics, in 21 countries. Previously untreated patients (≥18 years with an Eastern Cooperative Oncology Group performance status of ≤2) with stage III or IV classical Hodgkin lymphoma were randomly assigned (1:1) to receive A+AVD (brentuximab vedotin, 1·2 mg/kg of bodyweight, doxorubicin 25 mg/m of body surface area, vinblastine 6 mg/m , and dacarbazine 375 mg/m ) or ABVD (doxorubicin 25 mg/m , bleomycin 10 U/m , vinblastine 6 mg/m , and dacarbazine 375 mg/m ) intravenously on days 1 and 15 of each 28-day cycle for up to six cycles. Stratification factors included region (Americas vs Europe vs Asia) and International Prognostic Score risk group (low, intermediate, or high risk). The primary endpoint was modified progression-free survival; this 5-year update includes analysis of progression-free survival as per investigator assessment in the intention-to-treat population, which was an exploratory endpoint, although the 5-year analysis was not prespecified in the protocol. This trial is registered with ClinicalTrials.gov (NCT01712490) and EudraCT (2011-005450-60), and is ongoing. Between Nov 19, 2012, and Jan 13, 2016, 1334 patients were randomly assigned to receive A+AVD (n=664) or ABVD (n=670). At a median follow-up of 60·9 months (IQR 52·2-67·3), 5-year progression-free survival was 82·2% (95% CI 79·0-85·0) with A+AVD and 75·3% (71·7-78·5) with ABVD (hazard ratio [HR] 0·68 [95% CI 0·53-0·87]; p=0·0017). Among PET-2-negative patients, 5-year progression-free survival was higher with A+AVD than with ABVD (84·9% [95% CI 81·7-87·6] vs 78·9% [75·2-82·1]; HR 0·66 [95% CI 0·50-0·88]; p=0·0035). 5-year progression-free survival for PET-2-positive patients was 60·6% (95% CI 45·0-73·1) with A+AVD versus 45·9% (32·7-58·2) with ABVD (HR 0·70 [95% CI 0·39-1·26]; p=0·23). Peripheral neuropathy continued to improve or resolve over time with both A+AVD (375 [85%] of 443 patients) and ABVD (245 [86%] of 286 patients); more patients had ongoing peripheral neuropathy in the A+AVD group (127 [19%] of 662) than in the ABVD group (59 [9%] of 659). Fewer secondary malignancies were reported with A+AVD (19 [3%] of 662) than with ABVD (29 [4%] of 659). More livebirths were reported in the A+AVD group (n=75) than in the ABVD group (n=50). With 5 years of follow-up, A+AVD showed robust and durable improvement in progression-free survival versus ABVD, regardless of PET-2 status, and a consistent safety profile. On the basis of these findings, A+AVD should be preferred over ABVD for patients with previously untreated stage III or IV classical Hodgkin lymphoma. Millennium Pharmaceuticals (a wholly owned subsidiary of Takeda Pharmaceutical Company), and Seagen.